Curling ulcer in scalded patient: a case report - Sánchez, Omar Sosa; Espinosa, Mario A. Pineda; Pérez, Yoselin J. Sarabia; Montaño, Mónica Heredia; Barrientos, Cheryl Zilahy Díaz; Paredes, Raymundo García (International Journal of Research in Medical Sciences, 2025)
Stress-related gastrointestinal erosive syndrome is defined as the presence of erosions of the gastric mucosa originating from physiologically stressful events. SA "Curling Ulcers" which occur after burns involving more than 30% of the total burned body surface area. Its most frequent location is in the stomach or in the duodenum. We present the case of a 62-year-old male with 49% SCTQ burn. 3 weeks later presents data of probable bleeding of upper gastrointestinal tract so diagnostic endoscopy is performed and the presence of duodenal ulcer Forrest III is evidenced. This type of ulcer occurs primarily in patients with physiological stress, its management is focused on prophylaxis and should be suspected in those patients with high risk factors; when these are presented the management is conservative and the complete resolution after the basic pathology must be evidenced. At present treatment is not contemplated as a therapeutic action merely aimed at healing the ulcerative niche, the importance of treatment is to detect and properly classify those patients with high risk factors for the development of this type of ulcer and thus be able to initiate an adequate prophylaxis; same management that was performed in our patient for presenting risk factors, in addition to clinical compatible, and laparoscopic diagnosis of Curling ulcer, with adequate response; and subsequent follow-up that evidenced its complete resolution.